Teleprimary care in Malaysia: a tool for teleconsultation and distance learning in health care - Yadav, H.; Wong, Y.L. (SAGE Publications, 2001)
Malaysia enjoys a comprehensive range of health services, the government being committed to the principles of universal access to high quality health care, which the Ministry of Health provides through a wide variety of nation wide network of clinics and hospitals. One of the major problems is the availability of comprehensiveness and quality of health care in remote health centres. When patients are transferred from the health centres to the hospitals for further treatment, this not only incurs inconvenience to the patients and their family but also increases the cost to the health care system. Teleprimary care is one of the tools to overcome this problem. The doctors in the remote clinics are able to discuss the problem cases through teleconsultation with the doctors and specialist in the hospitals using an audiovisual system to provide better care in the health centers without transferring the patients to the hospitals. Only the essential and needy patients are referred to the hospitals. This has not only reduced the number of patients referred to the hospitals but it has reduced the cost to the health care system. It has also provided a more comprehensive care to the patients in the health centres. The doctors in the health centers are also provided training and are also updated on the latest in medicine. This method of training has made doctors in the health centers more efficient and satisfied.